Monogenic diabetes associated with PAX4 gene mutations (MODY9): first description in Russia - Natalya A. Zubkova (Endocrinology Research Centre, 2017)
Maturity-onset diabetes of the young (MODY) is a heterogeneous group of disorders characterised by autosomal dominant type of inheritance and caused by genetic defects leading to dysfunction of pancreatic beta-cells. To date, at least 13 subtypes of MODY have been described in the literature, the most frequent of which are MODY types 1–3. MODY2 and MODY3 are the most prevalent subtypes, and were previously described in our country, Russia. Several cases of rare MODY subtypes were subsequently described in the Russian literature. The current report is the first in the Russian literature to present clinical and molecular genetic characteristics of two cases of another rare MODY subtype—MODY9. This type of MODY is associated with mutations in the PAX4 gene, which encodes transcription factor PAX4, one of the factors essential for pancreatic beta-cell differentiation. Molecular genetic analysis was performed using next-generation sequencing, a new method recently applied to verify monogenic diseases and, in particular, MODY. This study reports a novel mutation in the PAX4 gene in MODY patients.